Advances in the estimation of body fat percentage using an artificial intelligence 2D-photo method - Tathiany J. Ferreira; Igor C. Salvador; Carolina R. Pessanha; Renata R. M. da Silva; Aline D. Pereira; Maria A. Horst; Denise P. Carvalho; Josely C. Koury; Anna P. T. R. Pierucci (npj Digital Medicine)
Abstract There is a growing need to evaluate the agreement between the field methods and integrate artificial intelligence (AI) using two-dimensional (2D) photos for enhanced real-world analysis. This study evaluated the agreement between AI-2D photos and the clinical reference method, dual-energy X-ray absorptiometry (DXA) to estimate the body fat percentage (BFP). Other methods were also investigated, including skinfolds, A-mode ultrasound, and bioelectrical impedance analysis (BIA). This cross-sectional study was conducted on 1273 adults of both sexes. The Bland–Altman plots, Lin’s Correlation Coefficient of Agreement (CCC), and error analyses were calculated. AI-2D photos demonstrated substantial agreement with DXA presenting the highest agreement (CCC ≥ 0.96) among all the investigated methods. InBody-270 and Omron HBF-514 BIA devices showed moderate agreement (CCC = 0.90 to 0.95) for all participants, age groups >30 years, and body mass index >25 kg/m2. AI-2D photos can be interchangeable with DXA, providing a practical, accessible alternative and an easy-to-use system for BFP estimation.